2020
DOI: 10.1057/s41287-020-00325-5
|View full text |Cite
|
Sign up to set email alerts
|

Intersecting Vulnerabilities: The Impacts of COVID-19 on the Psycho-emotional Lives of Young People in Low- and Middle-Income Countries

Abstract: Across diverse contexts, emerging evidence suggests that the COVID-19 pandemic is increasing levels of anxiety and stress. In calling for greater attention to people’s psychosocial and emotional well-being, global actors have paid insufficient attention to the realities of the pandemic in low- and middle-income countries, where millions of people are already exposed to intersecting vulnerabilities. Chronic poverty, protracted violence, conflict and displacement, coupled with weak health, education and protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
119
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(127 citation statements)
references
References 22 publications
(21 reference statements)
3
119
0
1
Order By: Relevance
“…Labeling individuals with a "functional" level of fear as "symptomatic" and in need of treatment may thus, paradoxically, diminish their adherence to protective behaviors and lead to increased transmission of SARS-CoV-2. Similarly, if psychological distress is an understandable reaction to high levels of social hardship, then offering individual psychological interventions may delay, or even divert attention from, the provision of necessary social and economic support-which may include financial aid, unemployment benefits, or supports to individuals, families and communities with a prior socioeconomic vulnerability (Hagen, 2011;Banati et al, 2020;Rajkumar, 2020b). A further concern with "medical" modes of treatment, particularly if pharmacological treatment is offered (which is often the case where trained therapists are not available), is that some pharmacological agents have the undesirable adverse effect of blunting empathy, particularly empathy evoked by exposure to the suffering of others (Rutgen et al, 2019).…”
Section: Conceptual Framework For Psychological Distress In the Context Of A Pandemic And Their Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Labeling individuals with a "functional" level of fear as "symptomatic" and in need of treatment may thus, paradoxically, diminish their adherence to protective behaviors and lead to increased transmission of SARS-CoV-2. Similarly, if psychological distress is an understandable reaction to high levels of social hardship, then offering individual psychological interventions may delay, or even divert attention from, the provision of necessary social and economic support-which may include financial aid, unemployment benefits, or supports to individuals, families and communities with a prior socioeconomic vulnerability (Hagen, 2011;Banati et al, 2020;Rajkumar, 2020b). A further concern with "medical" modes of treatment, particularly if pharmacological treatment is offered (which is often the case where trained therapists are not available), is that some pharmacological agents have the undesirable adverse effect of blunting empathy, particularly empathy evoked by exposure to the suffering of others (Rutgen et al, 2019).…”
Section: Conceptual Framework For Psychological Distress In the Context Of A Pandemic And Their Practical Implicationsmentioning
confidence: 99%
“…From a material perspective, access to unemployment insurance during the pandemic was associated with better mental health (Berkowitz and Basu, 2020). Conversely, it has been observed that individuals who were already living in adverse circumstances prior to the pandemic, and who had reduced access to several commonly available GRRs, were more likely to experience psychological distress during the pandemic (Banati et al, 2020).…”
Section: Evidence For the Relevance Of Salutogenic Factors During The Covid-19 Pandemicmentioning
confidence: 99%
“…As seen during the COVID-19 pandemic and the HIV epidemic, experiences of stigma have had a wide range of negative outcomes for children ( 34 , 74 ). In a study focusing on HIV treatment adherence, the authors note that interventions to reduce stigma should target multiple levels of influence - intrapersonal, interpersonal and structural - in order to have maximum effectiveness ( 75 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since the outbreak of Covid-19 at the beginning of 2020, emerging evidence suggests that the COVID-19 pandemic is increasing levels of anxiety and stress. [5] The situation is also true among children. At the end of February, 2020, in order to help ease the anxiety, spread anti-epidemic knowledge and promote understanding and friendship among countries, chairman of IBBY (International Board on Books for Young People) Zhang Mingzhou launched an initiative of providing free anti-epidemic picture books for children around the world.…”
Section: A Review Of the Programmentioning
confidence: 99%